Teacher Planning at Integrated Islamic Elementary School - Sukirdi Sukirdi; Suwarni Suwarni (AL-ISHLAH: Jurnal Pendidikan, 2021)
The planning process of a teacher entails numerous components. The elements pertaining to teachers include the teacher-student ratio, professional competence, and Iman and Taqwa (IMTAQ). The study's objective was to examine teacher planning at a Bengkulu-based Integrated Islamic Elementary School (SDIT). This study employs a qualitative methodology. The data collection technique use observation, documents, and interviews. The data analysis in this study was descriptive-analytic. The study's findings indicated that SDIT Bengkulu's teacher planning was carried out by a collegial collective team comprising a principal and five deputy principals. Six individuals acted as informants. Teacher planning's purpose is to ensure that the teacher-student ratio and teacher competencies, specifically teacher professionalism and religion, are met.